Body Image Concerns in People Who Underwent a Total Laryngectomy - Isabel Guimarães; Gabriela Torrejano; Raquel Aires; Filomena Gonçalves; Susana Vaz Freitas; Paula Correia; Cláudia Romeiro; Inês Silvestre; Rita Bom; Paulo Martins; Ana R. Santos (MDPI AG, 2024)
Background: Body image is a potential psychological burden after total laryngectomy (TL) with devastating effects on patients' health-related quality of life (HRQOL) and communication. This study focused on TL patients to determine the prevalence of dissatisfied body image and whether they have poorer HRQOL and difficulty adjusting to their new voice than TL patients with satisfied body image. It also aimed to investigate the potential predictors of body image. Methods: A multicenter cross-sectional study was conducted. For TL patients, the Body Image Scale (BIS), the European Organization for Research on Cancer Quality of Life Questionnaire, Core and Neck Module (EORTC QLQ C30 and EORCT H&N35), and the Self-Experiences of Communication after Laryngeal cancer (SECEL) were used. Patients were categorized as dissatisfied with their body image if the BIS score was ≥8. Multiple regression analysis was performed using the BIS as the dependent measure and HRQOL (QLQ C30 and H& N35) and communication (SECEL) as independent variables. Results: Overall, 31.3% of TL patients had dissatisfied body image, significantly worse HRQOL, and difficulty adjusting to their new voice than patients with satisfied body image. The regression model showed that social eating and socializing (H&N35) and adjustment to their new voice (SECEL) were independent predictors of body image. The model explained 52% of the variance. Conclusions: Screening TL patients at risk for body image concerns may help develop effective interventions to optimize HRQOL and patient communication.